Screening of Medicinal Plants against Aspergillus flavus - Ravi Kumar, Kalaichelvam (Universiti Malaysia Sarawak, (UNIMAS), 2018)
This project focused on antifungal activity of Azadirachta indica, Ficus religiosa and Mentha piperita leaves extract in order to evaluate the effect of methanol extracts against the most important phytopathogenic fungi, Aspergillus flavus_by poisoned food technique and disc diffusion technique. Different concentrations which were 100, 75 and 50 mg/ml of these extracts were found to inhibit the growth A. flavus. In the solvent extracts tested, Mentha piperita extract gave the highest percentage of inhibition which was 31.25% against Aspergillus flavus. The different concentration of methanol extracts has showen inconsistent percentage of growth of inhibition for Aspergillus flavus which it was slightly not effective in antifungal activity of Azadirachta indica, and Ficus religiosa.